The Influence of Service Quality and Information Quality on Repurchase Intention with Customer Satisfaction as an Intervening Variable during the Covid-19 Pandemic (At Pt Jasaraharja Putera Branch Manado) - Insan, Yamalul; Karamoy, Herman; Lengkong, Victor PK (International Journal on Economics, Finance and Sustainable Development (IJEFSD), 2023)
This research aims to 1)Analyzing the effect of Service Quality on Customer Satisfaction during a pandemic at the Manado branch of PT Jasaraharja Putera; 2) Analyze the effect of Information Quality on Customer Satisfaction during a pandemic at the Manado branch of PT Jasaraharja Putera; 3) Analyze the effect of Service Quality on Repurchase Intention during a pandemic at the Manado branch of PT Jasaraharja Putera; 4) Analyze the effect of Information Quality on Repurchase Intention during a pandemic at the Manado branch of PT Jasaraharja Putera; 5) Analyze the effect of Customer Satisfaction on Repurchase Intention during a pandemic at the Manado branch of PT Jasaraharja Putera. This research was conducted at PT Jasaraharja Putera Manado Branch. The sample used in this research is a customer who buys back at PT Jasaraharja Putera Manado Branch, a total of 140 customers. The data collection technique used is a questionnaire. This research is a type of quantitative research using path analysis techniques (path analysis). This study also uses the Partial Least Square (PLS) analysis model to obtain latent variable relationships and to predict construct structural indicators. The results showed that there was a significant influence between service quality on customer satisfaction, as indicated by a significance value of P values of 0.00 <0.05, which means that there was a significant effect between service quality variables on customer satisfaction. There is an insignificant effect between the variable quality of information on customer satisfaction as indicated by the significance value of P values of 0.19>0.05. It can be concluded that there is no significant effect of information quality on customer satisfaction. There is a significant effect between service quality on repurchase intention with a significance value of P Values 0.02 <0.05. There is no significant effect between the quality of information on repurchase intention, as indicated by the significance value of P values of 0.09>0.05. It can be concluded that the quality of information does not significantly influence repurchase intention. There is a significant influence between customer satisfaction as a moderating variable on repurchase intention P values of 0.00>0.05.